Advanced nanocomposite-based electrochemical sensor for ultra-sensitive dopamine detection in physiological fluids - Shinde, Megha; Slaughter, Gymama (Frontiers in Lab on a Chip Technologies, 2025)
This study presents a novel point-of-care electrochemical sensor for dopamine (DA) detection, featuring a flexible laser-induced graphene (LIG) modified with a unique nanocomposite comprising Nb4C3Tx MXene, polypyrrole (PPy), and iron nanoparticles (FeNPs). The LIG-Nb4C3Tx MXene-PPy-FeNPs is characterized by scanning electron microscopy to confirm the successful surface modification. The electrochemical performance of the fabricated sensor via cyclic voltammetry showed significant electrochemical activity upon Nb4C3Tx MXene-PPy-FeNPs nanocomposite modification of the LIG surface with an increased peak anodic current (Ipa) from 43 μA to 104 μA. The sensor demonstrated high electrocatalytic activity and a wide linear detection range of 1 nM to 1 mM DA with excellent sensitivity of 0.283 μA/nM cm−2, and an ultralow detection limit of 70 pM. The LIG-Nb4C3Tx MXene-PPy-FeNPs sensor exhibited good recovery in biological samples and a remarkable selectivity for DA, effectively distinguishing it from common interfering compounds such as uric acid, ascorbic acid, glucose, sodium chloride, and their mixtures. This flexible LIG-Nb4C3Tx MXene-PPy-FeNPs sensor platform provides a reliable and accurate approach for detecting DA, even in complex biological matrices at point-of-care applications highlighting its potential for advanced biosensing applications.